PET/CT in Hepatobiliary and Pancreatic Malignancies (PET/CT,, 2018)
This book is a pocket guide to the role of PET/CT in malignancies of the hepatobiliary system and pancreas. Imaging findings characteristic of malignancies are described and illustrated, and attention drawn to normal variants and artifacts. In addition, information is presented on epidemiology, clinical presentation, pathology, staging, and management in order to provide the clinical insight required by the imaging specialist. The book will be of immense value to practicing nuclear physicians as well as hybrid imaging specialists, particularly during reading sessions and multidisciplinary team meetings. It will also serve as a quick reference for residents and fellows in the PET/CT department. The book is published within the series Clinicians' Guides to Radionuclide Hybrid Imaging, which is compiled under the auspices of the British Nuclear Medicine Society. The series is the joint work of professionals worldwide who share a common vision in promoting nuclear medicine as an important imaging specialty for the diagnosis and management of oncological and non-oncological conditions.